Pengelolaan Surat Masuk dan Surat Keluar - Azizah, Novia Farah; Kuswantoro, Agung (Universitas Negeri Semarang, 2021)
The result of this research are to know that the process of managing incoming and outgoing letters. This study uses descriptive qualitatife research. The informant source of four administrative management employees and four general employess based on the purposive sampling technique. The results of this research are : the stages in the process of managing incoming letters are 1) receiving letters, 2) sorting, 3) attacing sheets disposition, 4) recording, 5) briefing, 6) follow-up, 7) storage. The stage in managing the outgoing letters are 1) drafting the letters, 2) tiered examination, 3) management approval, 4) recording and numbering process, 5) storage, 6) distribution. Concluded in this research is1) the recording of incoming letters using the agenda book of the letter of entry, dipsosis sheet, and E-Office, 2) the creation of a letter referring to the regulation of the head of the national archive number 2 the year 2014 on the layout of the manuscript,3) letter numbering based on mayor regulation number 33 of 2013 on the classification pattern of Semarang city government archives,4) E-Office exit letter has not been used.. The advice given is 1) increase the number of archivists and facilities of mail storage infrastructure,2) the process of recording incoming mail is carried out after getting a disposition by the head so that the recording is not done twice,3) need unity of understanding between the mail management staff, with the socialization related to the management of the office script, 4) E-Office outgoing mail is used to help the process of mail management.